Socio-Cultural Risks and the Quality Of Life of Female Children in Africa - ESIRI, May (International Journal of Psychosocial Rehabilitation, 2020)
This study examines socio-cultural risk factors and the extent to which they affect the quality of life of female children in Africa, by obtaining empirical evidence from Nigeria, one of the prominent countries of the continent. By relying on the cross-sectional survey design, primary data were however obtained from a sample of 225 respondents through a self-structured questionnaire and administered to young female adults and parents of female children (men and women). The research instrument was validated and pre-tested for content and construct validity. The level of reliability of the questionnaire was established by the result of the Cronbach’s Alpha test which obtained an overall reliability coefficient of 0.9624. Analysis of the data was done using measures of central tendencies and the structural equation model technique based on the constructs of the stochastic frontier model. Overall, we observe that child and adolescent marriages, adolescent pregnancies and female genital mutilation were among the key socio-cultural risk factors believed to have a significant influence on the quality of life of female adolescents in Africa generally and Nigeria in particular. Additionally, we found that gender-based violence, child labour and trafficking does not exert significant influence on the quality of life of adolescents in the region. Based on the above, it was recommended amongst others that Nigeria and other African countries, though the help and assistance of international bodies should enact strict laws prohibiting child marriages and female genital mutilation. Appropriate strict sanctions should also be placed on offenders.